2002
DOI: 10.1108/03055720210471139
|View full text |Cite
|
Sign up to set email alerts
|

Trends in integrated library systems

Abstract: Provides an overview of the present state of development of integrated library systems and identifies, describes and evaluates significant trends in the industry in relation to their context within the overall development of library services. Notes that the library systems market, and developments in library systems, are driven by Internet trends and by the software Industry rather than by the library and information community and that they are subject to global economic imperatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A very comprehensive article on trends in integrated library systems was written by Ebenezer and published in 2002. Its foci are developments in Web technologies and standards in relation to ILMSs, overall software industry developments and enhancements in functionality and information access from the user's perspective, and she identifies several of the trends discussed below (Ebenezer, 2002). She observed that trends within the IT industry in general are being reflected in library systems, and this has also been noted elsewhere (Kochtanek, 2001).…”
Section: Trends In Integrated Library Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…A very comprehensive article on trends in integrated library systems was written by Ebenezer and published in 2002. Its foci are developments in Web technologies and standards in relation to ILMSs, overall software industry developments and enhancements in functionality and information access from the user's perspective, and she identifies several of the trends discussed below (Ebenezer, 2002). She observed that trends within the IT industry in general are being reflected in library systems, and this has also been noted elsewhere (Kochtanek, 2001).…”
Section: Trends In Integrated Library Systemsmentioning
confidence: 99%
“…They allow systems staff in libraries to modify the vendor's software to fit local requirements, and also allow faster upgrading of software. This could be a very useful facility for libraries which enjoy systems support from skilled computing staff (Chvatal and Shoffner, 2003; Ebenezer, 2002).…”
Section: Trends In Integrated Library Systemsmentioning
confidence: 99%
See 3 more Smart Citations